Prospects of Algolization of Rice Fields in Osh Oblast - Israilova, Gulbarchin Salimovna; Abdyrakhmanova, Zhazgul Suyunbaevna; Zhusupov, Baigeldi Turgumbaevich; kyzy, Guliza Mamatisa; Ermekbaev, Nurbek Zhakypovich (Research in Ecology, 2025)
The article discusses the prospects of using algae in the soil—to improve the fertility of rice fields in the Osh oblast of Kyrgyzstan. The authors note that the Fergana Valley, where Osh oblast is located, is an important rice-growing region, and there are currently plans to expand rice fields. In this regard, the study of methods to increase rice yields, such as algolization, is of particular relevance. The article emphasizes that rice fields are unique aquatic ecosystems where microorganisms, especially algae, play an important role. Algae, particularly blue-green algae (cyanobacteria), are capable of fixing nitrogen from the air and enrich the soil with it, which is especially important for rice, which needs nitrogen for growth. The algolization method helps to improve soil structure, reduce the need for mineral fertilizers, control weeds and is an environmentally friendly method of fertility improvement. The authors provide data on the species composition of cyanobacteria found in rice fields in Osh oblast, noting the predominance of Chroococcus and Hormogonium forms. They also indicate seasonal fluctuations in algae abundance associated with climatic conditions. In conclusion, the authors highlight the promising application of algolization in rice farming in Osh oblast and the need for further research to identify the most effective algal species and develop optimal methods of their application.